Entertaining Children The Participation of Youth in the Entertainment Industry - Arrighi, G.; Emeljanow, V.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Children have been exploited as performers and wooed energetically as consumers throughout history. These essays offer scholarly investigations into the employment and participation of children in the entertainment industry with examples drawn from historical and contemporary contexts.
Keywords: Performing arts; Theater—History.; Youth—Social life and customs; Arts; Theater; Childhood; Adolescence; Performing Arts; Theatre History; Youth Culture; Arts; Theatre and Performance Studies; Childhood, Adolescence and Society